2016
DOI: 10.1080/08990220.2016.1178634
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive predictors of balance in Parkinson’s disease

Abstract: Postural instability is one of the most incapacitating symptoms of Parkinson's disease (PD) and appears to be related to cognitive deficits. This study aims to determine the cognitive factors that can predict deficits in static and dynamic balance in individuals with PD. A sociodemographic questionnaire characterized 52 individuals with PD for this work. The Trail Making Test, Rule Shift Cards Test, and Digit Span Test assessed the executive functions. The static balance was assessed using a plantar pressure p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…VR dual-task gait training involves executive function,19 a predictor of balance deficits in patients with PD 48. VR tasks involve gait control and meet environmental demands (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…VR dual-task gait training involves executive function,19 a predictor of balance deficits in patients with PD 48. VR tasks involve gait control and meet environmental demands (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we examined the effect of cognitive function in postural control via the DCCS task and found that PDPI+ participants performed the task poorly, compared to PDPI− and controls. Similar to our results, previous reports have shown a reduction in cognitive function in PD patients with abnormal balance and postural control (48,49), suggesting a dysfunction of common neural networks in PDPI+. Furthermore, this relationship is supported by previous studies' results with lower theta activity in the frontal region at the occurrence of target stimuli during a cognitive task (24,26,50).…”
Section: Discussionsupporting
confidence: 92%
“…A previous study showed that more cognition-related regions, such as caudate, fusiform gyrus and inferior parietal lobes35, were affected in PIGD patients. One study reported that cognitive performance was a predictor of postural control in individuals with PD36. PD patients could increase attention to counteract the balance disturbance in late stage37, therefore, PD patients exhibited more impaired postural control in the cognitive-motor dual-task condition in later stage because of distraction by cognitive task.…”
Section: Discussionmentioning
confidence: 99%